Diversified Polyketides With Anti-inflammatory Activities From Mangrove Endophytic Fungus Daldinia eschscholtzii KBJYZ-1 - Wang, Guisheng; Yin, Zhenhua; Wang, Senye; Yuan, Yilin; Chen, Yan; Kang, Wenyi (Frontiers in Microbiology, 2022)
In total, five new polyketide derivatives: eschscholin B (2), dalditone A and B (3 and 4), (1R, 4R)-5-methoxy-1,2,3,4-tetrahydronaphthalene-1,4-dio (5), and daldilene A (6), together with 10 known as analogs (1, 7–15) were isolated from the mangrove endophytic fungus Daldinia eschscholtzii KBJYZ-1. Their structures and absolute configurations were established by extensive analysis of NMR and HRESIMS spectra data combined with ECD calculations and the reported literature. Compounds 2 and 6 showed significant cell-based anti-inflammatory activities with IC50 values of 19.3 and 12.9 μM, respectively. In addition, western blot results suggested that compound 2 effectively inhibits the expression of iNOS and COX-2 in LPS-induced RAW264.7 cells. Further molecular biology work revealed the potential mechanism of 2 exerts anti-inflammatory function by inactivating the MAPK and NF–κB signaling pathways.